2022
DOI: 10.3390/ijerph19148438
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Working Hours Flexibility and Well-Being Prior to and during COVID-19 in South Korea

Abstract: Objective: This study examined the relationship between the flexibility of work schedule arrangements and well-being among full-time workers prior to and after the coronavirus disease (COVID-19) outbreak in South Korea. Methods: Data from the fifth 2017 and sixth 2020–2021 Korean Working Conditions Survey, including a final sample of 45,137 participants (22,460 males; 22,677 females), were used. Multiple logistic regression was performed to establish the association between schedule arrangement types and the 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Work time flexibility can be achieved based on formal or informal organizational practices [78]. When employees feel supported and encouraged by their organizations to manage non-work demands or challenges at work, such as when organizations give employees work time flexibility to care for children or family members, they are more likely to put forth greater effort in developing skills and personal effectiveness to manage their work and non-work demands and responsibilities, which increases their well-being [79] and also has a positive impact on their perception of psychological empowerment.…”
Section: Hypothesis Development 221 Flexible Work Arrangements and Ps...mentioning
confidence: 99%
“…Work time flexibility can be achieved based on formal or informal organizational practices [78]. When employees feel supported and encouraged by their organizations to manage non-work demands or challenges at work, such as when organizations give employees work time flexibility to care for children or family members, they are more likely to put forth greater effort in developing skills and personal effectiveness to manage their work and non-work demands and responsibilities, which increases their well-being [79] and also has a positive impact on their perception of psychological empowerment.…”
Section: Hypothesis Development 221 Flexible Work Arrangements and Ps...mentioning
confidence: 99%
“…Additionally, higher job control can encourage employees to learn new things because they will perceive their work as more challenging [ 25 ]. Research by Joudrey and Wallace [ 34 ] and Nerobkova et al [ 35 ] revealed that having control over deciding how many hours to work can decrease depression, while employees will feel more empowered if their tasks are clearly defined [ 36 ]. Social support, presented through colleague and supervisor support, is a significant stimulus for employees’ development and well-being [ 25 , 36 ].…”
Section: Introductionmentioning
confidence: 99%